Evaluation of an Instrumented Horseshoe System - Field, J. R.; Schnurr, D.; Horney, F. D. (Veterinary and Comparative Orthopaedics and Traumatology, 1992)
A commercially available instrumented horseshoe, designed to quantitate a fraction of the vertical component of the ground reaction force (Fz), underwent a series of mechanical evaluations. This followed the occurrence of considerable variability in transducer output in response to a given load.The mechanical evaluation of this system revealed many factors that contributed to the variability in transducer output. The primary factor appeared to be the disruption to the transducer required in its calibration in the laboratory and subsequent placement in the horse-mounted system. This requirement introduced significant (P <0.05) variability into the system.A preliminary evaluation of the system when mounted on horses only succeeded in adding to the variability in transducer output.In view of the many contributors to transducer output variability it is concluded that as the system is currently designed it does not allow for accurate or reproducible quantitation of force transmission, in either the laboratory or when mounted on horses.An instrumented horseshoe underwent a series of mechanical evaluations. Many factors contributed to variability in transducer output recorded. It was concluded that the system, as currently designed, does not provide accurate or reproducible quantification of the vertical force component (Fz).
Keywords: Instrumented horseshoe; ground reaction force